Clinical Trials and their Impact on Society - Olga Lidia Cuevas Pérez; Ana María Molina Gómez; Diana Rosa Fernández Ruiz (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2016)
Today there are countless examples that illustrate the nature of technoscience, including biotechnology and pharmacology. The clinical trial is the appropriate methodology used by clinical pharmacology to test the efficacy and safety of a treatment or intervention in humans. It constitutes the cornerstone of research. Once the preclinical research is completed, one of the biggest challenges currently facing the Cuban Pharmaceutical and Biotechnological Industry is precisely the clinical evaluation. Therefore, this work aims to provide a reflection on the most significant aspects of clinical trials and their impact on society.